Child Adoption Cases in Sabah Syariah Courts - Nooryasmensharini Abas; Suraya Sintang (Penerbit UMS, 2019)
Under the Sabah Syariah Courts Enactment 2004, the Sabah State Syariah Court has exclusive jurisdiction of all actions and proceedings pertaining to the Application of Child Adoption by Muslims. No other state in Malaysia provides their Syariah courts with similar exclusive provisions in matters pertaining to child adoption for Muslims. This study examines child adoption cases that had been decided by the Sabah State Syariah Courts and proposes improvements to the current procedures. Data collection for this study relied on (i) analysis of documents on cases registered with the Sabah State Syariah Courts and (ii) interviews with the relevant officers. The outcome of this study seeks to provide insights to Muslims in Sabah on the processes of child adoption application under the jurisdiction of the Sabah State Syariah Courts.